Effects of chronic Rhodiola Rosea supplementation on sport performance and antioxidant capacity in trained male: Preliminary results - Duranti, G.; Parisi, A.; Ciminelli, E.; Ceci, R.; Cerulli, C.; Quaranta, F.; Tranchita, E.; Borrione, P.; Sabatini, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Rhodiola Rosea (RR), is an adaptogen plant, that belongs to Crassulaceae family, that has been reported to affect several physiological mechanisms, stimulating metabolism, promoting fatty acids utilisation, having an ergogenic function, improving body resistance to physical strenuous efforts [1,2] and showing an antioxidant function [3]. The purpose of this study is to investigate the effects of chronic Rhodiola Rosea supplementation on physical performance parameters, redox status and the capacity of substrate consumption during endurance exercise in a group of competitive athlets. We selected 14 well trained male athletes, between 20 and 35 years old. After an admission test evaluating the maximal oxygen uptake (VO2 max), the subjects underwent a chronic supplementation with Rodhiola Rosea (170 mg/die) or placebo (P) every morning for 4 weeks in a double blind clinical trial. At the end of supplementation period, the athletes underwent the cardio-pulmonary exhaustion test at 75% of their VO2 max. Physical performance parameters evaluated show that HR Max (171±10 for P vs 172±8 bpm for RR), the Borg Scale level (all 4-5), VO2 max (49.86±12.75 for P vs 52.61±12.35 ml/kg/min for RR) and duration of the test (19±9 for P vs 19±11 min for RR) are essentially the same after Rhodiola Rosea or placebo intake. Rhodiola Rosea reduced in a statistically significative manner (p<0.05 at acme and p<0.01 after 30 minutes recovery) plasma free fatty acids levels in supplemented group (12.86±1.62 for P vs 7.31±1.31 mgFFA/dl plasma for RR at acme and 11.41±0.56 for P vs 7.01±1.16 mgFFA/dl plasma for RR after 30 minutes recovery). No effect on blood glucose was found. Blood antioxidant status (Haemolysis, Total Antioxidant Status, Manoldialdheyde) and inflammatory (Interleukine-6) parameters results unaffected after RR supplementation. Blood lactate (p<0.05) and plasma creatine kinase (all p<0.01) levels decreases in a statistically significative way in Rhodiola Rosea group compared to placebo (37.19±7.29 for P vs 23.50±3.96 U-CK/L plasma for RR at acme and 35.52±4.20 for P vs 25.70±5.24 U-CK/L plasma for RR after 30 minutes recovery). In conclusion, we demonstrate that a chronic Rhodiola Rosea supplementation can be useful for sports activity, during endurance exercise by decreasing lactate levels, parameters of skeletal muscle damage as creatine kinase and ameliorating fatty acid consumption.